2015
DOI: 10.1080/08927936.2015.1052272
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological and Physiological Effects of Using a Therapy Dog in Mindfulness Training

Abstract: Research from various fields has demonstrated the benefits of human-animal interaction for physical and mental health. Recently, animal-assisted therapy (AAT) has become increasingly popular in a variety of healthcare settings-including inpatient mental health care facilities. However, there is limited research investigating the efficacy of AAT in outpatient sites. In addition, the impact of animals as an adjunct to psychotherapy treatment remains mostly uninvestigated. Therefore, it is necessary to empiricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 64 publications
1
5
1
1
Order By: Relevance
“…Active control interventions are usually expected to produce beneficial effects regardless of their specifc contents 55 . This explanation is in line with an earlier study comparing a modified MBSR-intervention with and without animal-assistance for clients experiencing psychological distress where all participants experienced fewer anxiety and depressive symptoms, decreased psychological distress, and increased mindfulness skills from pre- to post-treatment with no significant difference between groups 54 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Active control interventions are usually expected to produce beneficial effects regardless of their specifc contents 55 . This explanation is in line with an earlier study comparing a modified MBSR-intervention with and without animal-assistance for clients experiencing psychological distress where all participants experienced fewer anxiety and depressive symptoms, decreased psychological distress, and increased mindfulness skills from pre- to post-treatment with no significant difference between groups 54 .…”
Section: Discussionsupporting
confidence: 88%
“…Alliance ruptures in psychotherapy may occur with either the therapist or the animal, but usually not with both 49 . Studies show that integrating an animal into psychotherapy can lead to higher treatment adherence 53 , higher ratings of therapist efficacy and willingness to participate in future mindfulness trainings for clients experiencing psychological distress 54 . Although first evidence regarding the benefit of animal-assistance in psychotherapy exists, research of differences in application and modes of action regarding animal-assistance is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to our hypothesis, there was no significant group × time interaction effect on any of the variables, however, there was a significant effect of time on loneliness, as measured by the UCLA-LS, whereby loneliness significant reduced over time. This lack of a group × time interaction effect is in contrast to positive dog interaction and DAM group effects reported previously [16,17]. Despite the lack of quantitative findings supporting group differences in the current study, qualitative insights revealed several encouraging owner-related themes such as 'relaxed/calm', 'mindful/focussed/attentive/engaged, 'fun/enjoyable/happy' and 'connected with dog'.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings from this study suggest both mindfulness practices and dog interactions act as effective techniques for the self-management of wellbeing, which may also act as a protective barrier against loneliness. Henry and Crowley [17] found that including dogs within mindfulness practice did not result in any additional benefits when compared to a mindfulness practice alone in terms of reduction in symptoms of psychological distress, or the acquisition of mindfulness skills, however, participants did report higher ratings of the training and endorsed future participation more highly in the dog assisted mindfulness group. Considering how challenging mindfulness practices can be to learn and maintain (for example, [18,19]), the presence of a dog may help with participant adherence to a mindfulness program and/or increase motivation and engagement.…”
Section: Introductionmentioning
confidence: 91%
“…Gress [140] criteria for inter-library loan not met Haggerty et al [141] wrong study design Hammer et al [142] wrong study design Hemingway et al [143] wrong study design Henry [144] wrong intervention…”
Section: References Of Excluded Studies From Full Manuscript Search Reason Excludedmentioning
confidence: 99%